Factors for inhibition of early discharge from the psychiatric emergency ward for elderly patients - Sho Adachi; Tomoko Komiya; Kenji Nomura; Masayuki Shima (Komiyama Printing Co. Ltd, 2018)
Abstract Background As society is aging, the number of elderly patients with psychiatric disorder, such as dementia, is increasing. The hospitalization period of elderly patients in psychiatric wards tends to be prolonged. In this study, we have determined the factors that inhibit early discharge from the psychiatric emergency ward for elderly patients in Japan. Methods The information was collected from patients admitted to our hospital's emergency ward for elderly patients with psychiatric disorders between May 2015 and April 2016. We compared various factors between the early discharge group and the non-early discharge group. In addition, we used a multiple logistic regression model to clarify the risk factors for non-early discharge. Results Of the 208 elderly patients, body mass index (BMI) and serum albumin level were significantly lower in the non-early discharge group. In addition, we also showed that higher serum C-reactive protein (CRP) (> 0.5 mg/dL) and use of seclusion or physical restraint significantly inhibited the early discharge of patients. The results of multiple logistic analysis showed that the BMI ≤ 17.5 kg/m2 (OR, 2.41 [95% confidence interval (CI) 1.06-5.46]), serum albumin level ≤ 30 g/L (OR, 3.78 [95% CI 1.28-11.16]), and use of seclusion or physical restraint (OR 3.78 [95% CI 1.53-9.37]) are particularly important explanatory factors. Conclusions Hypoalbuminemia, low BMI, and the use of seclusion or physical restraint were identified as the factors that inhibit early discharge from the psychiatric emergency ward for elderly patients. These factors reflect malnutrition and extremely serious psychiatric symptoms.